Gestión administrativa y la ejecución presupuestal en la Gerencia Regional de Salud Loreto 2022 - Chong Fernandez, Gloria Erika (2022)
The general objective of the research was to determine the relationship between administrative management and budget execution in the Regional Health Management Loreto 2022, where an applied type study was chosen, with a correlational level and a non-experimental design, made up of a population of 85 workers. For data collection, the survey technique has been used, using a questionnaire of questions. The work concluded that the relationship between administrative management and budget execution in the Regional Health Management Loreto 2022, was considerable positive r = 0.747 and a significance of p = 0.000. At the same time, a coefficient and a significance of (r=0.732; p=0.000) for planning were determined. Likewise, organization presents a coefficient and a significance of (r=0.490; p=0.000). In addition, direction presents a coefficient and a significance of (r=0.717; p=0.00). And for control, a coefficient and a significance (r=0.643; p=0.000). Therefore, each of them is significantly related to budget execution.